Analytical Simulation of Flow and Heat Transfer of Two-Phase Nanofluid (Stratified Flow Regime). (25th March 2014) - Abbasi, Mohammad; Baniamerian, Zahra
Abstract : Nanofluids have evoked immense interest from researchers all around the globe due to their numerous potential benefits and applications in important fields such as cooling electronic parts, cooling car engines and nuclear reactors. An analytical study of fluid flow of in-tube stratified regime of two-phase nanofluid has been carried out for CuO, Al2 O2, TiO3, and Au as applied nanoparticles in water as the base liquid. Liquid film thickness, convective heat transfer coefficient, and dryout length have been calculated. Among the considered nano particles, Al2 O3 and TiO2 because of providing more amounts of heat transfer along with longer lengths of dryout found as the most appropriate nanoparticles to achieve cooling objectives.